Effect of an ultra-endurance event on cardiovascular function and cognitive performance in marathon runners - Perrotta, A. S.; Jeklin, A. T.; Bredin, S. S. D.; Shellington, E. M.; Kaufmann, K. L.; de Faye, A.; Miles, M.; Warburton, D. E. R. (Frontiers in Physiology, 2022)
Background: Ultra-marathon running participation has become increasingly more popular in recent years; however, there is inconclusive evidence concerning the effects of participation on cognition and cardiovascular function. The purpose of this study was to examine alterations in cardiovascular function and cognitive performance and their association in ultra-marathon runners prior to and following an ultra-endurance event.